The energy transition in action: domestic fuel choices in a changing Zimbabwe - Campbell, Bruce M.; Vermeulen, Sonja J.; Mangono, J.J.; Mabugu, R. (2003)
Two questionnaire surveys of fuel use by low-income households in Zimbabwe were conducted in four small towns in 1994, and in these towns plus four larger towns in 1999. An energy transition from wood through kerosene to electricity occured (a) with rising household income, (b) with increasing electrification status among towns and (c) over time in the smaller towns, in spite of falling household incomes in two of the towns. Increasing discrepancy in the incomes of higher and lower income groups over time was not associated with greater divergence in their fuel choices. By 1999 electricity was used by almost all households in towns with good electricity supplies, while use of firewood in these towns was infrequent. However, even the wealthiest households continued to combine electricity with other fuels, usually kerosene. Electricity use by less affluent households is apparently limited to lack of connections in the home and by access to appliances, while fuel prices, which are subject to government subsidies and fell in real terms over 5 years, have been less important. Zimbabwe's urban domestic energy policy has had considerable success in terms of equity, but this is increasingly difficult to maintain given present economic and political uncertainty.